The effectiveness of community-based rehabilitation for providing services to people with stroke with functional limitations and participation restriction : a systematic review and implications - Naidoo, Lionel Edmund (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 59-63).